LANGUAGE(S) OF POSTCOLONIALITY – HISTORY OF POSTCOLONIAL STUDIES – AN OVERVIEW - Kołodziejczyk, Dorota (Porównania, 2014)
The language of postcolonial studies which, as in other languages, is difficult to locate, from the beginning has been distinguished by its hybridizing force. It emerged as a particular version of poststructuralism after taking over the Saidian language and, for two decades, it developed as a virtual Babel tower of materialism, feminism and gender studies, deconstruction, Lacanian and Freudian psychoanalysis, and, later on, globalization studies, cosmopolitism, ecocriticism and po st-humanism. In this hybridizing hotch-potch of languages of theory what surprises is a relative monolinguality of the discipline – postcolonial studies speaks in the language of the empire and it has never prioritized the task of protecting or promoting literary languages, some of which are disappearing. The article poses questions about the task of translation and comparison in postcolonial studies.